2016
DOI: 10.1002/pits.21937
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Adolescents’ Perceptions of Teacher-Student Relationships and Their Academic Self-Regulation: Does Liking a Specific Teacher Matter?

Abstract: Although positive teacher‐student relationships are known to aid students’ academic self‐regulation, the emotional aspects of teacher liking are often neglected within research. The present study used a large sample of seventh‐ and eighth‐grade students (N = 1,088; MAge =  13.7) in secondary schools in Germany to investigate whether the motivation students gain from specific well‐liked teachers (i.e., that students identify) can moderate the relation between their perception of teacher‐student relationships ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 61 publications
(81 reference statements)
1
30
0
2
Order By: Relevance
“…Relationships have long been established as a critical element of youth development. In educational settings, research has demonstrated that student-teacher relationships can influence students’ academic engagement, motivation, and achievement (Archambault, Janosz, & Chouinard, 2012; Bernstein-Yamashiro & Noam, 2013; Collie, Martin, Papworth, & Ginns, 2016; Cornelius-White, 2007; Goodenow, 1993; Hughes & Cao, 2017; Kannapel & Clements, 2005; Lee, 2012; Raufelder, Scherber, & Wood, 2016; Sointu, Savolainen, Lappalainen, & Lambert, 2017; Vollet, Kindermann, & Skinner, 2017; Wang, 1990; Wentzel, Russell, & Baker, 2016; Wentzel, 2009, 2012). The benefits of strong student-teacher relationships extend beyond such proximal factors related to academic success, and are also associated with factors related to the broader school context, such as perceptions of school climate (Adams, Ware, Miskell, & Forsyth, 2014), a feeling of belonging or connectedness (Cohen, McCabe, Michelli, & Pcikerall, 2009), and improved student behavior (Bernstein-Yamashiro & Noam, 2013).…”
Section: Student-teacher Developmental Relationshipsmentioning
confidence: 99%
“…Relationships have long been established as a critical element of youth development. In educational settings, research has demonstrated that student-teacher relationships can influence students’ academic engagement, motivation, and achievement (Archambault, Janosz, & Chouinard, 2012; Bernstein-Yamashiro & Noam, 2013; Collie, Martin, Papworth, & Ginns, 2016; Cornelius-White, 2007; Goodenow, 1993; Hughes & Cao, 2017; Kannapel & Clements, 2005; Lee, 2012; Raufelder, Scherber, & Wood, 2016; Sointu, Savolainen, Lappalainen, & Lambert, 2017; Vollet, Kindermann, & Skinner, 2017; Wang, 1990; Wentzel, Russell, & Baker, 2016; Wentzel, 2009, 2012). The benefits of strong student-teacher relationships extend beyond such proximal factors related to academic success, and are also associated with factors related to the broader school context, such as perceptions of school climate (Adams, Ware, Miskell, & Forsyth, 2014), a feeling of belonging or connectedness (Cohen, McCabe, Michelli, & Pcikerall, 2009), and improved student behavior (Bernstein-Yamashiro & Noam, 2013).…”
Section: Student-teacher Developmental Relationshipsmentioning
confidence: 99%
“…We measured students' mathematics interest because student interest in academic domains is related to social dimensions such as student-teacher relationships and students' need for belongingness (Bergin, 1999(Bergin, , 2016Raufelder et al, 2016;Walton, Cohen, Cwir, & Spencer, 2012). Students' interest in academic domains is also associated with academic engagement, self-efficacy, and achievement (Bergin, 2016;Tosto et al, 2016;Upadyaya & Eccles, 2014).…”
Section: Students' Mathematics Interestmentioning
confidence: 99%
“…Furthermore, the quality of student-teacher relationships can be particularly important in middle school (Eccles et al., 1993; McCollum & Yoder, 2011; Wentzel et al., 2010). For example, when middle school students perceive positive social supports from their teachers, they show increased academic interest and higher levels of engagement compared to peers without such relationships (Raufelder, Scherber, & Wood, 2016; Roorda et al., 2011; Wentzel, Baker, & Russell, 2012; Wentzel et al., 2010). A meta-analysis focused on adolescent students found an effect size of 0.40 between student-teacher relationships and school engagement and an effect size of 0.20 between student-teacher relationships and achievement (Roorda et al., 2011).…”
mentioning
confidence: 99%
“…The link between teacher perception and readiness to study the subject is rather intuitive, but it is also based on previous research. For example, Raufelder, Scherber and Wood () found that when early adolescent students could identify a well‐liked teacher, they tended to have higher levels of academic motivation. What is more, students’ motivation based on liking a single teacher compensated for generally low‐quality teacher‐student relationships and had an impact on students’ intrinsic motivation (Raufelder et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Raufelder, Scherber and Wood () found that when early adolescent students could identify a well‐liked teacher, they tended to have higher levels of academic motivation. What is more, students’ motivation based on liking a single teacher compensated for generally low‐quality teacher‐student relationships and had an impact on students’ intrinsic motivation (Raufelder et al ., ). Teachers and parents are often viewed as the most important contributors to students’ achievement because they have direct interaction with children themselves, and play a direct role in developing and maintaining the motivation to study (Barbarin & Aikens, ; Kendal, Keeley & Callery, ).…”
Section: Introductionmentioning
confidence: 99%